An orbital floor fracture may not always be the cause of new‐onset diplopia: Literature review of the aetiology and types of diplopia. (15th July 2015) - Kyriakidou, E.; O'Connor, N.; Larkin, E.B.
Abstract: Persistent diplopia is a well‐recognised complication following orbital trauma. Other sequelae include limited extraocular movement and enophthalmos. Rarely co‐existing causes may account for these symptoms. We report a case where delayed repair of right orbital floor and medial wall fractures did not lead to resolution of the diplopia and the strabismus in the right eye. Further investigations including haematological and biochemistry indices revealed low thiamine levels related to previous excess alcohol misuse. Once treated with thiamine supplement, a remarkable improvement in their eye symptoms was observed.